1999
DOI: 10.1038/sj.bjc.6690689
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis in human breast and colorectal cancer

Abstract: Summary Proteolysis occurs when proteinase activity exceeds inhibitor activity. Proteolysis is normally tightly regulated and is involved in cancer invasion and metastasis. The aim of this study was to compare proteolysis in breast and colorectal cancer. Proteinase and inhibitor expression were analysed in paired tumour and normal tissue samples from 43 breast and 24 colorectal cancer patients using substrate zymography, Western blotting and quenched fluorescence substrate hydrolysis. The expression of the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 32 publications
4
48
0
1
Order By: Relevance
“…These observations are consistent with previous observations on active and proform MMP-2 and proMMP-9 (Liabakk et al, 1996). The presence of active MMP-9 has also been described before (Yamagata et al, 1991;Garbett et al, 1999a;Zeng et al, 1999;Baker et al, 2000), but quantitative measurement in all samples had not been reported up until now. Active MMP-2 increases more than its proform in tumour tissue.…”
Section: Molecular and Cellular Pathologymentioning
confidence: 79%
See 1 more Smart Citation
“…These observations are consistent with previous observations on active and proform MMP-2 and proMMP-9 (Liabakk et al, 1996). The presence of active MMP-9 has also been described before (Yamagata et al, 1991;Garbett et al, 1999a;Zeng et al, 1999;Baker et al, 2000), but quantitative measurement in all samples had not been reported up until now. Active MMP-2 increases more than its proform in tumour tissue.…”
Section: Molecular and Cellular Pathologymentioning
confidence: 79%
“…To some degree, all show enhanced gelatinase levels in tumour tissue, at least for the latent forms of MMP-2 and MMP-9. However, some studies (Liabakk et al, 1996;Parsons et al, 1998) have not quantified active MMP-9, while others (Garbett et al, 1999a;Zeng et al, 1999;Baker et al, 2000) do not report specific activities but rather the absence or presence of the various enzyme forms. A consistent quantification of both the latent and active forms -and their ratio -of both gelatinases in matched tumour and normal tissue is still lacking.…”
mentioning
confidence: 99%
“…MMP-9 (gelatinase B) is over-expressed in both breast and colorectal cancer (Garbett et al, 1999). Of the many identified polymorphisms in the MMP-9 gene, two (a (CA)n microsatellite polymorphism at position -90 and a single nucleotide polymorphism at position -1562) are functionally significant (Shimajiri et al, 1999;Zhang et al, 1999a).…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…In many pathological conditions, modifications of their expression profile causes the lost of balance in the ECM homeostasis. Several studies demonstrated the association between MMP9 and tumour progression in breast [6][7][8][9], colorectal [9] and prostate cancer [10]. MMP9, also known as gelatinase B, is a 92 kDa type IV collagenase secreted as inactive glycosylated precursor and subsequently activated by the removal of 73 amino acids at the NH 2 terminus.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, TIMP-1 has a selective binding with the pro-MMP-9 and is considered the main inhibitor for MMP-9 [13,15]. The detection of MMP9 expression has been performed in lung cancer by immunohistochemistry [1,7,[15][16][17][18][19], zymography [9,10,18,20], immunoenzymatic assays [21] and Northern analysis [8,15]. Increased plasma levels of MMP-9 protein were also detected in lung cancer patients [22,23].…”
Section: Introductionmentioning
confidence: 99%